Efficacy Of Pgf2α And Hcg For Improving Reproductive Performance In Cyclic Cows Under Field Condition - Makode, S.B.; Pawshe, C.H.; Deshmukh, S.G.; Ingawale , M.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Total 50 normal cyclic cows were selected and equally divided into 5 different groups. Group I and II cows were treated with 2 ml injection of normal saline 11 days apart. Cows from group III, IV and V were treated with PGF2α injection 11 days apart. Cows from group IV and V were treated with hCG 1500 IU i/m at the time of AI and after 11 days of AI, respectively. Cows of group II, III, IV, V received pre-synchronization medicinal treatment (PSMT) comprising mineral mixture @ 50 g daily for 15 days orally, Ivermactin) @ 1 ml per 50 kg body weight s/c, Vitamin AD3E 5 ml i/ m and sodium acid phosphate 10 ml i/m 15 days prior to estrus synchronization treatment. Out of 30 cows in group III, IV and V, 25 (83.33 %) cows responded to first dose and all 30 (100 %) responded to 2nd dose of PGF2α. The average mean time required for onset of estrus (for pooled 30 PG treated cows) after 1st and 2nd PGF2α injection was 81.20 ± 4.66 and 74.40 ± 1.01 hrs, respectively, and the average mean length of estrus was 15.68 ± 0.77 and 17.33 ± 0.47 hrs, respectively. The conception rates in groups I, II, III, IV and V was 0, 20, 40, 50 and 40 %, respectively.
Keywords: Estrous synchronization; conception rate; hCG